2007
DOI: 10.1111/j.1460-9568.2007.05302.x
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of human retinotopic visual cortex to S‐cone‐opponent, L/M‐cone‐opponent and achromatic stimulation

Abstract: Our aim was to make a quantitative comparison of the response of the different visual cortical areas to selective stimulation of the two different cone-opponent pathways [long- and medium-wavelength (L/M)- and short-wavelength (S)-cone-opponent] and the achromatic pathway under equivalent conditions. The appropriate stimulus-contrast metric for the comparison of colour and achromatic sensitivity is unknown, however, and so a secondary aim was to investigate whether equivalent fMRI responses of each cortical ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
120
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(133 citation statements)
references
References 56 publications
11
120
2
Order By: Relevance
“…Even though many visual regions are generally responsive to color, the above mentioned brain regions actually prefer chromatic stimuli over achromatic stimuli (e.g. Bartels & Zeki, 2000;Mullen, et al, 2007), which may explain why we find adaptation effects exactly in those regions.…”
Section: Discussionmentioning
confidence: 79%
“…Even though many visual regions are generally responsive to color, the above mentioned brain regions actually prefer chromatic stimuli over achromatic stimuli (e.g. Bartels & Zeki, 2000;Mullen, et al, 2007), which may explain why we find adaptation effects exactly in those regions.…”
Section: Discussionmentioning
confidence: 79%
“…Other fMRI measurements, which analyzed the mean response by visual area, have shown and characterized cone opponency in V1 and V2 but found no evidence of unipolar representations for simple stimulus display (Engel et al 1997;Liu and Wandell 2005;Mullen et al 2007Mullen et al , 2008Wandell et al 1999). Taking advantage of metacontrast display, the present study was able to find evidence for unipolar representations by a conventional analysis of mean response.…”
Section: Implications For Cortical Color Representationsmentioning
confidence: 99%
“…When comparing the target color component with the luminance component in cone contrast units, the color component was 2.2 times smaller than the luminance component. Consequently, when we assume that human V1 has about 2-6 times greater sensitivity for color than for luminance (Engel et al 1997;Liu and Wandell 2005;Mullen et al 2007Mullen et al , 2008Parkes et al 2009), ϳ50 -70% of the observed neural suppression would reflect the color response, disregarding the fact that the relative sensitivity to color and luminance depends on spatial and temporal aspects of stimuli. Apart from the degree of inherent color contribution to suppression, the suppression is clearly a consequence of the action of a color mechanism, because our target and mask were equiluminant.…”
Section: Neural Correlates Of Color Visibilitymentioning
confidence: 99%
“…Similarly, Parkes et al, 6 having measured the fMRI BOLD responses to°ickering radial patterns composed of perceptual colors (red, green, yellow, blue), found that the BOLD responses evoked were similar, even though the individual di®erences with respect to each color pattern were su±ciently reliable to predict the color viewed. Mullen et al, 7 having measured the fMRI BOLD response in the visual cortex to radial chromatic red/green and yellow/ blue grating patterns di®ering either in cone activation or in multiples of detection threshold, determined that the amplitude of the BOLD response was not linearly related to either measure. In their later investigation of the response of early and extra-striate visual areas to color, speci¯cally highcontrast red-green (RG), they found that the most evident in the early visual areas (V1 and V2), but selective responses, revealed as greater adaptation between the same stimuli than cross-adaptation between di®erent stimuli, emerged in the ventral cortex, in V4 and VO in particular.…”
Section: Introductionmentioning
confidence: 99%
“…It should come as no surprise, then, that color stimulation and detection in the visual cortex have been the subjects of long-standing study and debate. [1][2][3][4][5][6][7][8][9][10][11][12][13] The objective of the present study is to characterize appropriate features of the hemodynamic response (HR) signals obtained from the visual cortex upon color stimuli. Five di®erent features (i.e., mean, slope, peak, skewness, and kurtosis) of the obtained HR signals are examined in order to classify the three di®erent color stimuli (i.e., red, green, and blue (RGB)).…”
Section: Introductionmentioning
confidence: 99%